Dissolution and evolution effects on pressure fluctuations in a space micropump - Zhipeng Ren; Honglei Hao; Deyou Li; Hongjie Wang; Jintao Liu; Yong Li (SAGE Journals, 2022)
The purpose of this paper is to reveal the dynamic mass transfer effects between gas and liquid on pressure fluctuations in a space micropump using our proposed computational model of gas–liquid mass transfer. Complex dissolution and evolution processes were applied to achieve accurate dynamic gas–liquid mass transfer predictions in the micropump. The validation of experiments was conducted by measuring the performance characteristics of the micropump, and the mass transfer model was verified by a dissolved oxygen concentration experiment in plug discharge flow. Based on this, four conditions including unsteady single-phase, two-phase without mass transfer, dissolution, and coexisting dissolved–released flows calculations are discussed to clarify the frequency contents, generation reasons, and propagation law. Combined with entropy production analysis, the pressure fluctuation influenced by the dissolution and evolution is illustrated. The results exhibit that the evolution of the gas is located on the head of the long blade suction surface in the impeller. When a unidirectional gas-to-liquid dissolution process occurs, the fluctuating amplitude of the characteristic dominant 5fn is significantly weakened; otherwise, when dissolution and evolution coexist, the amplitude is significantly promoted as the released gas increase the flow instability. In addition, the distributions of local high entropy production induced by mean and fluctuating velocity gradients overlap that of large mass transfer rates and high amplitude of the mixing frequency in the volute, exhibiting the relationship between entropy production, mass transfer, and flow instability. The current study provides a guidance that the dissolved gases’ concentration must be controlled strictly to avoid the evolution of gas for the safety and stability of the space hydraulic system.
Keywords: Engineering not elsewhere classified; Materials Engineering not elsewhere classified